Design and implementation of multi-node data transmission system based on MLVDS and USB3.0 - Wang Hongliang; Wang Liuming (Dianzi Jishu Yingyong, 2019)
Aiming at the problem that the host computer can not communicate with the multi-node acquisition device at high speed in the distributed data acquisition system,a data converter based on MLVDS interface and USB3.0 interface is designed. The converter uses CYUSB3014 interface chip to achieve high-speed data transmission between computer and FPGA, uses ADN4693E interface chip to complete multi-node data transmission, uses FPGA as the core controller, and resolves multi-node communication logic based on MLVDS custom protocol to implement data interaction between MLVDS interface and USB3.0 interfaces. The test results show that the data conversion result of the converter is accurate and reliable, and the high-speed communication between the host computer and the multi-node data acquisition equipment is realized.